2007
DOI: 10.4103/0970-1591.33442
|View full text |Cite
|
Sign up to set email alerts
|

Testicular microlithiasis: Is there an agreed protocol?

Abstract: This review addresses the issues on etiopathogenesis of testicular microlithiasis (TM), associated clinical entities, evaluation and follow-up of patients with TM. A literature search of Medline/PubMed was carried out using the keywords ‘testicular microlithiasis’ and ‘testicular calcifications’ for published data in English language on TM from 1970 to 2006. TM is an uncommon entity among adult males, resulting from intratubular calcifications. The reported incidence of TM is highly variable. With the increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…The diagnostic criterion for TM was the detection of more than three inclusions (with a diameter of 1–3 mm) without acoustic shadowing in testicular parenchyma. 6 …”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic criterion for TM was the detection of more than three inclusions (with a diameter of 1–3 mm) without acoustic shadowing in testicular parenchyma. 6 …”
Section: Methodsmentioning
confidence: 99%
“…Testicular microlithiasis (TM) is characterized by multiple, small, uniform-appearing echogenic foci of less than 3 mm without acoustic shadowing in the seminiferous tubules, which may be indicative of degeneration of the testicular parenchyma [ 11 , 12 ]. Several theories about the origin or causes of TM have been reported, however, the exact etiology of TM still remains unclear [ 13 ]. Previous studies have reported an association between TM and testicular germ cell tumors and/or carcinoma in situ [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Известно, что микролиты могут формироваться одновременно в органах половой, дыхательной и нервной систем, что, возможно, связано с пока еще не установленными генетическими дефектами. Оказалось, что ТМ чаще наблюдают у физически менее активных и социально неблагополучных мужчин, а также среди тех, кто употребляет много картофельных чипсов и попкорна [10,11]. ТМ нередко сопровождает другие заболевания -крипторхизм, гипогонадизм, перекрут яичка, варикоцеле, гидроцеле, сперматоцеле, а также неходжкинские лимфомы, муковисцидоз, синдромы Клайнфельтера и Дауна [3,12,13], а анализ 17 публикаций позволил также сделать вывод о снижении фертильности при ТМ, что дало основание предположить наличие связи между ТМ и синдромом тестикулярной дисгенезии [11].…”
Section: Introductionunclassified